CRISPR/Cas9-Targeted Mutagenesis in Caenorhabditis elegans - Waaijers, Selma (Genetics Society of America, 2013)
The generation of genetic mutants in Caenorhabditis elegans has long relied on the selection of mutations in large-scale screens. Directed mutagenesis of specific loci in the genome would greatly speed up analysis of gene function. Here, we adapt the CRISPR/Cas9 system to generate mutations at specific sites in the C. elegans genome.